Playing with the big boys basketball, American imperialism, and subaltern discourse in the Philippines - Antolihao, Lou (Lincoln University of Nebraska Press, 2015)
""Playing with the Big Boys" traces the development of basketball in the Philippines from and educational to tool during the early period of American colonial rule in the early twentieth century to a ubiquitous national pastime".
Includes biographical references and index.
Keywords: Basketball -- Philippines -- History; Basketball -- Social aspects -- Philippines; Filipinos -- Social life and customs